The Role of Philosophy in Contemporary Religious Education : A Dialogical Approach - Gilang Muhammad; Febria Aini; Delia Natalie Valentina (Green Philosophy: International Journal of Religious Education and Philosophy, 2024)
Philosophy plays a vital role in nurturing religious education by encouraging critical thinking and ethical inquiry. This study explores the dialogical relationship between philosophy and religion in an educational context, emphasizing how philosophical frameworks can help students engage with complex theological questions. The paper also highlights the benefits of integrating philosophical discussions into religious curricula to enhance moral reasoning and intercultural dialogue.